2015
DOI: 10.1002/cctc.201402923
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Oxidative Esterification of Benzyl Alcohol and Acetaldehyde over Gold Supported on Nanostructured Ceria–Alumina Mixed Oxides

Abstract: Au nanoparticles supported on nanostructured ceria‐alumina mixed oxides (10 and 30 wt % ceria) were prepared by a deposition–precipitation method. Their properties were studied by N2 adsorption, XRD, TEM, X‐ray photoelectron spectroscopy, and UV/Vis spectroscopy under temperature‐programmed reduction or oxidation. The materials catalyzed the liquid‐phase aerobic oxidative esterification of benzyl alcohol and benzaldehyde effectively and showed a much better performance than Au supported on the individual oxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…It is worth noting that gold catalysts prepared by sol-gel and supported on CeO2-Al2O3 mixed oxides are more active than Au on CeO2 or Al2O3 in the base-free benzaldehyde oxidative esterification in benzyl alcohol, despite the lower Au content [94]. Interestingly, the most active systems are those possessing surface Lewis acid sites with weak and medium strength.…”
Section: Catalyst Design Optimization Of Gold Catalysts Supported Onmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that gold catalysts prepared by sol-gel and supported on CeO2-Al2O3 mixed oxides are more active than Au on CeO2 or Al2O3 in the base-free benzaldehyde oxidative esterification in benzyl alcohol, despite the lower Au content [94]. Interestingly, the most active systems are those possessing surface Lewis acid sites with weak and medium strength.…”
Section: Catalyst Design Optimization Of Gold Catalysts Supported Onmentioning
confidence: 99%
“…Au supported on ceria-alumina mixed oxides was proved to be a very efficient and highly stable catalyst for the aerobic oxidative esterification of benzyl alcohol and acetaldehyde [94]. The Au catalyst supported on a mixed oxide containing 30 wt % CeO 2 was reused after a first catalytic run to convert another amount of substrate without significant loss of activity and selectivity.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Reverse oxygen spill over occurred at the perimeter of the Au nanoparticles, and these gold sites were showed to be involved in the activation of methanol. Indeed, the activity of gold catalysts supported on CeO 2 −Al 2 O 3 mixed oxides was attributed to the oxygen storage capacity of the support …”
Section: Introductionmentioning
confidence: 99%
“…In particular, partially reducible metal oxides (like CeO 2 and TiO 2 ) as the supports were found rather effective in enhancing the activity of Au catalysts; as reported by Abad and co-workers, Au nanoparticles loaded on the CeO 2 nanocrystals rich in oxygen vacancies demonstrated excellent catalytic performance in the oxidation of alcohols, with a TOF similar to that achieved over the Pd-based catalysts . Smolentseva and co-workers also reported that Au supported on nanostructured ceria–alumina-mixed oxides (Ce–Al oxides) was catalytically active in the aerobic oxidative esterification of benzyl alcohol; depending on the composition of Ce–Al composite oxide, the activity of the Au/Ce–Al catalyst increased in the order of Au/Al 2 O 3 < Au/CeO 2 < Au/Ce 10 –Al < Au/Ce 30 –Al.…”
Section: Introductionmentioning
confidence: 99%